An Analysis on Cloud Security and the Function of Data Security Protocols (International Journal of Food and Nutritional Sciences, 2022)
A variety of services are now available to end users thanks to the development of cloud computing. Due to its advantages, most sectors are now able to leverage the cloud for their applications. Most cloud platforms have security holes and are vulnerable to several attacks. This study reviews the several security protocols that businesses may take, as well as some of the more specialized security procedures including authentication, authorization, encryption, as well as security systems. The processes for each safety measure are also looked at. Giving a basic overview of cloud computing security is the aim of this study. An explanation of cloud computing security, including its definition and scope, is provided. An ecosystem for cloud security is given to demonstrate the capabilities of each industry stakeholder. The security implications of cloud security are then considered for companies and operators. This study will present a new investigator as well as try to highlight the substantial security concerns and issues that emerge in public cloud systems, particularly with regard to data storage, administration, and processing.